ANALISIS MANAJEMEN PENGELOLAAN OBAT DI PUSKESMAS LANGGAM KABUPATEN PELALAWAN - Seprina, Zurni; Fitria, Eliza; Realita, Nelfa (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
The availability of adequate and quality drugs in service facilities is determined by good drug management resources and management. Langgam Health Center has drug vacancies in the Puskesmas drug warehouse, this is a serious problem because it causes losses and disappointment to the community. This study aims to analyze drug management at Langgam Health Center which includes Human Resources, Facilities and Infrastructure, Planning, Procurement, Receiving, Storage, Distribution, Destruction, Control and Administration. The design of this research is qualitative using the method of in-depth interviews with five informants, observation by making direct observations and documentation at the Langgam Health Center, Pelalawan Regency in August 2023. The results of the research obtained are the management of drug management at the Langgam Health Center of Pelalawan Regency, the Human Resources of drug managers at the Puskesmas are not in accordance with the Minister of Health Regulation Number 74 of 2016, The occurrence of drug vacancies and damaged drugs due to a planning system that does not meet the standards. It greatly affects the supply of drugs in health services. Suggestions for the Langgam Health Center and the Pelalawan Regency Health Office to establish a balance in the drug management management cycle, planning with the consumption method can be considered for use in the context of budget efficiency and to minimize the occurrence of stagnant and stockout drugs and the potential for drug expiration.Keywords: Management; Medicine; Health Center